Anatomia Kranz, estructura y distribucion de cloroplastos en hojas de yuca (Manihot esculenta Crantz) - Riano, N.M.; Cock, James H.; López F., Y.; El-Sharkawy, Mabrouk A. (1987)
To determine the presence of Kranz anatomy, chloroplast structure and distribution in cassava leaf tissues, a selection was made among materials of CIAT`s germplasm bank. Two materials were selected, var. MCol 22 and hybrid CM 507-37; work was also carried out with maize var. Swan Laposta C48B (monocotyledonous C4 plant), Amaranthus dubius (dicotyledonous C4 plant), and an advanced bean line (dicotyledonous C3 plant). Leaves of the different species were cut and observed under both optical and electronic microscopes to determine the differences or similarities between cassava plants and standard C3/C4 plants. Important differences were observed in cassava leaves in relation to each standard. Parenchyma palisade tissue occupies almost 70 percent of the leaf thickness, forming a funnel-like structure. A crown of cells larger than those of the surrounding spongy parenchyma was observed; chloroplasts were arranged in centrifugal position, similar to the typical Kranz anatomy of C4 plants. The ultrastructural differentiation of the chloroplasts, located in spongy and palisade parenchyma and in the crown around the vascular bundle, in spite of not yet being clear, evidences the possible function of the crown around the vascular bundle, explaining the biochemical and photosynthetic performance of the plant. (AS)